REPRESENTATION OF WOMEN IN HINDI CINEMA: AN ANALYTICAL STUDY (International Journal of Food and Nutritional Sciences, 2022)
Purpose: Hindi cinema plays a very important role in impacting people’s lives and it also plays a role in constructing and deconstructing gender roles and stereotypes. This study shows how women have been portrayed in the last twenty years, that is from 2000-2020, in Hindi Cinema. Bollywood movies reflect the practices that take place in our societies. This research was important to understand the portrayal of women and to find out if there is any evolution or devolution of women characters.